Thalamic deep brain stimulation for orthostatic tremor: a multicenter international registry - Merola, Aristide; Wolf, Marc (Movement disorders, 2017)
Background We report the accumulated experience with ventral intermediate nucleus deep brain stimulation for medically refractory orthostatic tremor. Methods Data from 17 patients were reviewed, comparing presurgical, short-term (0-48 months), and long-term (≥48 months) follow-up. The primary end point was the composite activities of daily living/instrumental activities of daily living score. Secondary end points included latency of symptoms on standing and treatment-related complications. Results There was a 21.6% improvement (P = 0.004) in the composite activities of daily living/instrumental activities of daily living score, which gradually attenuated (12.5%) in the subgroup of patients with an additional long-term follow-up (8 of 17). The latency of symptoms on standing significantly improved, both in the short-term (P = 0.001) and in the long-term (P = 0.018). Three patients obtained no/minimal benefit from the procedure. Conclusions Deep brain stimulation of the ventral intermediate nucleus was, in general, safe and well tolerated, yielding sustained benefit in selected patients with medically refractory orthostatic tremor.